Analisis Nilai Religius Novel Cinta dalam Diam Karya Shineeminka - Ridho Kurniawan; Yuannisah Aini Nasution (Journal on Education, 2024)
This research contains a study of religious values in the novel Cinta in Silence by Shineeminka. The method used in this research is descriptive qualitative so that it can produce the required data in the form of quotation words. The data sources used in this novel are primary and secondary data sources. The primary data source is in the form of the novel Cinta in Silence by Shineeminka in 2017, while the secondary data sources are books and journals that are relevant to this research. The data collection technique in this research is to use reading and note-taking techniques in the novel Cinta in Silence by Shineeminka. The results of the analysis show that there are four religious values in the novel Cinta in Silence by Shineeminka, namely (1) The relationship between humans and God, namely: Belief in Allah which is owned by the characters Zahra, Ali, Mother Zahra, Andra, Anisa, Danang, Nisya, Father Zahra, and Ayana; Prayers that are owned by all characters in the novel; Praying performed by the character Zahra; Tawakkal performed by Zahra figures. (2) The relationship between humans and humans, namely: filial piety by Zahra and Ali; Good morals carried out by figures Zahra and Ali; The bad morals practiced by the character Ayana; Sincerity carried out by the character Zahra. (3) Human relations with oneself, namely: Maintaining self-respect by Ali and Zahra figures; Gratitude made by the figures of Zahra, Ali, Andra, Citra, Anisa, and Ayana; Honest figures owned by Ali and Zahra. (4) The relationship between humans and Nature is shown by the recognition of God's greatness.